Development of Stem-Esd E-Modules to Improve Students’ Integrated Problem-Solving Competencies in Grade 10 Students’ - Ardiansyah, Faizal Arqi; Suhendar; Setiono (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2025)
This study aims to develop a STEM-ESD (Science, Technology, Engineering, Mathematics - Education for Sustainable Development) e-module to train integrated problem-solving competencies in environmental change material. The method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. The research subjects involved 62 grade 10 students from a school in Sukabumi City. Validation scores from material, language, and media experts were 98%, 92%, and 94% (very high), respectively. The effectiveness of the e-module was evaluated using an actual experiment with a pretest-posttest control group design. The theoretical implications of this study lie in the development of integrated STEM-ESD tools using the Engineering Design Process (EDP) approach, which remains limited in the context of the Independent Curriculum. The analysis results showed a significant increase in students’ integrated problem-solving competency in the experimental class, with an N-Gain value of 0.62 (medium category), compared to the control class, which only achieved 0.22 (low category). Furthermore, user responses to the e-module showed excellent ratings in terms of appearance, language, ease of use, and visual appeal. Overall, the STEM-ESD e-module is practical and effective in enhancing learning outcomes and environmental awareness, while directly supporting SDG 12 (Responsible Consumption and Production) and SDG 13 (Climate Action). This module has the potential to serve as an innovative solution for sustainability-oriented learning in secondary schools. This e-module has the potential to be an innovative solution in supporting sustainability-oriented learning at the secondary school level.